Plasma IL-17, IL-35, interferon-?, SOCS3 and TGF-? levels in pregnant women with preeclampsia, and their relation with severity of disease - Ozkan, Zehra Sema; Simsek, Mehmet; Ilhan, Fulya; Deveci, Derya; Godekmerdan, Ahmet; Sapmaz, Ekrem (Taylor & Francis Ltd, 2014)
Objective: To research the hypothesis of preeclampsia (PE) is associated with increased systemic inflammatory responses of Th1-type as well as decreased Th2-type responses; we evaluated the maternal plasma levels of IFN-gamma, TNF-alpha, TGF-beta, IL-4, IL-6, IL-10, IL-17, IL-35 and SOCS3 in preeclamptic and healthy pregnants. Methods: This study was conducted with 40 preeclamptic (study group) and 40 normotensive pregnant (control) women in third trimester when they were admitted to the labor and delivery unit. The extracted maternal plasma samples were assayed by an enzyme-linked immunosorbent assay. Statistical analysis was performed by SPSS 16.0 version. Results: While IFN-gamma and TGF-beta levels of preeclamptic women were significantly higher (p<0.01), IL-35 and IL-17 levels of preeclamptic women were significantly lower (p<0.01) than those of controls. The ratios of IFN-gamma/IL-10, IFN-gamma/IL-6, IFN-gamma/IL-4 were significantly high and ratio of IL-35/IL-17 was significantly low in the PE group compared to those in the control group. Maternal plasma SOCS3 levels showed negative correlation with blood pressure and proteinuria severity, but none of the cytokines showed influence on blood pressure and proteinuria after adjusting for maternal and gestational age. Conclusions: Increased IFN-gamma/TGF-beta production and reduced IL-35/IL-17/SOCS3 production in preeclamptic women may lead to less cytokine inhibitory activity in PE, which may account for the increased proteinuria and blood pressure in PE.
Keywords: IL-17; IL-35; inflammation; preeclampsia; SOCS3